Embedded electronic system for evaluation of photovoltaic modules based on a current-voltage curve tracer - Ricardo Yauri; Rafael Espino (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
The rapid growth of the market for the use of renewable energy has increased the use of solar energy which has a significant role in power generation. This requires the insertion of equipment capable of providing precise measurements of the photovoltaic modules, either to verify the operation of the installation or to find specific problems. In this scenario, the current versus voltage curve tracer is used to describe the electrical behavior of the photovoltaic system through all the operating possibilities, but it has an excessive cost for small installations. This paper presents the development of a current-voltage curve tracer, capable of performing current, voltage and power measurements, contributing to the creation of equipment to test photovoltaic installations. The methods to obtain the I-V curves are presented and the characteristics of the embedded electronic system, which is based on an electronic load, are defined. As results, the simulations carried out for the variable load control, acquisition circuits and the implemented system are shown. In addition, the operation of the human-machine interface and the comparison with a commercial equipment are shown for reference.